Novel PV Simulator Based on Reactive Power Adjustment of PWM Rectifier - BAI Jiancheng; JIN Xinmin; JING Long; DAI Linwang (Kongzhi Yu Xinxi Jishu)
A PV array simulator was presented based on three-phase voltage PWM rectifier. Generally, PWM rectifier works at unity power factor, but the grid limits DC voltage range. Thus reactive current was provided via the grid to realize the simulator output in low voltage range. Furthermore, it analyzed the range of reactive current and proposed optimal methods. A converter connecting a three-phase resistance was used in the experiment, and dSPACE controlled the converter to simulate DC adjustable load, by changing load power to make the simulator work at different places of I-V curve. The ControlDesk monitored the I-V and P-V curves of the simulator at different light intensity. The experiment proves that the simulator can output I-V curve at different light intensity, and has wide voltage range.